VANGL2 downregulates HINT1 to inhibit the ATM-p53 pathway and promote cisplatin resistance in small cell lung cancer - Jiayi Xie; Huiying Liu; Chunqian Yang; Weitao Shen; Jian Zhang (Cell Death Discovery)
Abstract Cisplatin is a first-line drug for the treatment of small cell lung cancer (SCLC). Although the majority of patients with SCLC initially respond to cisplatin therapy, cisplatin resistance readily develops, leading to tumor progression. Therefore, this study aims to elucidate the mechanisms underlying cisplatin resistance in SCLC. We found that VANGL2 is a poor prognostic factor and promotes cisplatin resistance in SCLC. Mechanistically, in cisplatin-resistant cells, VANGL2 overexpression leads to the autophagic degradation of HINT1. This reduction in HINT1 expression further reduces the phosphorylation of ATM and p53 induced by cisplatin-mediated DNA damage. The decreased phosphorylation of p53 inhibits downstream apoptotic pathways, thereby reducing cisplatin-induced apoptosis. In conclusion, VANGL2 regulates the ATM-p53 pathway-mediated apoptotic response of SCLC to cisplatin by downregulating HINT1, thereby promoting cisplatin resistance. Thus, VANGL2 may serve as a potential therapeutic target for reversing cisplatin resistance in SCLC patients.